2019
DOI: 10.1016/j.spinee.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Paraspinal muscle cross-sectional area predicts low back disability but not pain intensity

Abstract: Background and context: The lumbar paraspinal muscles, including the erector spinae and multifidus, play an important role in movement and control of the spine. However, our understanding of their contribution to low back pain and disability is unclear. Systematic reviews have reported conflicting evidence for an association between paraspinal muscle size and low back pain, and a paucity of data examining muscle cross-sectional area and low back disability. Purpose: To investigate the relationship between para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 30 publications
9
52
0
Order By: Relevance
“…The multifidus muscle at L5/S1 has been shown to be affected more than other vertebral levels in response to de-loading (Hides et al, 2007; Belavy et al, 2011), acute and chronic LBP (Hides et al, 1996, 2011) and in response to exercise interventions (Hides et al, 2008, 2012; Welch et al, 2015). The observation that size of the multifidus muscles at L4 and L5 predicts disability associated with LBP, reinforces the premise that these lower levels require special attention when prescribing exercise (Ranger et al, 2018). The position of the lumbo-sacral junction has been monitored closely in astronaut reconditioning to allow progression to weightlifting and endurance training for astronauts (Petersen et al, 2017).…”
Section: Current Exercise Countermeasures On the Isssupporting
confidence: 66%
See 1 more Smart Citation
“…The multifidus muscle at L5/S1 has been shown to be affected more than other vertebral levels in response to de-loading (Hides et al, 2007; Belavy et al, 2011), acute and chronic LBP (Hides et al, 1996, 2011) and in response to exercise interventions (Hides et al, 2008, 2012; Welch et al, 2015). The observation that size of the multifidus muscles at L4 and L5 predicts disability associated with LBP, reinforces the premise that these lower levels require special attention when prescribing exercise (Ranger et al, 2018). The position of the lumbo-sacral junction has been monitored closely in astronaut reconditioning to allow progression to weightlifting and endurance training for astronauts (Petersen et al, 2017).…”
Section: Current Exercise Countermeasures On the Isssupporting
confidence: 66%
“…Results were conflicting for the other muscles (Ranger et al, 2017). CSA of the multifidus muscles was predictive of LBP for up to 12 months in men (Ranger et al, 2017) and CSA of the multifidus and erector spinae muscles at the L4 and L5 vertebral levels predicted low back disability (Ranger et al, 2018). Fatty infiltration of paraspinal muscles may result in loss of muscle function and impaired strength (Lang et al, 2010).…”
Section: Changes In Trunk Muscles Associated With Low Back Pain and Smentioning
confidence: 99%
“…Paraspinal muscle morphology and size have been of particular interest in studies investigating low back pain (LBP). Still, how lumbar muscle characteristics is an explaining factor for LBP is far from explicit 1,2,3742 . A great need for longitudinal studies has been addressed to evaluate causality in this matter 1,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that a small cross-sectional area (CSA) of paraspinal muscles predicts low back pain and disability 1,2 . Age-related structural changes in the lumbar spine, including CSA, morphology and composition, have been widely examined in cross sectional studies 17 , but longitudinal studies in this area are scarce 1,8,9 . The need for long-term cohort studies on this matter has been addressed 1 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation